Phylogenetic analysis supporting the taxonomic revision of eight genera within the bacterial order Enterobacterales. Issue 12 (30th December 2020) - Soutar, Craig D.; Stavrinides, John
Abstract : The diverse members of the Enterobacterales are agriculturally and medically relevant species that have continued to undergo taxonomic revision. To assess the current taxonomy of 64 genera of the Enterobacterales, we carried out a phylogenetic analysis using 32 single-copy core proteins. The resulting phylogeny was robust, and shows that eight genera – Biostraticola, Enterobacillus, Gibbsiella, Limnobaculum, Izhakiella, ' Nissabacter ', Rosenbergiella and Samsonia – are currently assigned to incorrect families. Taxonomic reassignment of these genera was also supported by average amino acid identity comparisons. We propose taxonomic revision of these genera to reflect their phylogenetic position within the Enterobacterales .